Quantum Chemical-Based Investigations and Lipophilicity Evaluations on Some Structurally Related Quinazoline Derivatives - Serin, Sümeyya (Orbital: The Electronic Journal of Chemistry, 2024)
This work was chiefly conceived to explore the substituent effects on thermodynamic, electronic and lipophilic characteristics of some quinazoline derivatives (Q1-Q4) from theoretical aspects. The variations caused by methyl, ethyl, chlorine and bromine substituents on the same carbon of the aromatic ring were evaluated with a computational approach. In accordance with this purpose, simultaneously, DFT-based calculations were performed for vacuum and two different surroundings (DMSO and water) on methaqualone (Q1), etaqualone (Q2), mecloqualone (Q3), and mebroqualone (Q4) compounds by using the B3LYP functional and 6-311++G(d, p) split-valence triple zeta basis set.  The computed thermodynamic quantities revealed that the halogen substitution was more preferable. The effect of substituent modification on electrostatic surface features was evaluated visually by molecular electrostatic potential (MEP) mapping technique. To shed light on the chemical reactivity behaviors of the Q1-Q4, DFT-based reactivity identifiers were computed. Also, the intramolecular interactions affected by substitution were evaluated on the basis of the Natural Bond Orbital (NBO) theory. The NBO results revealed that π-π* interactions predominate for each compound. The lipophilic character analyzes of the mentioned compounds were evaluated both numerically and visually. The data of both methods support each other.